MICROBIAL EXTRACTION OF CHITIN AND CHITOSAN FROM PLEUROTUS SPP, ITS CHARACTERIZATION AND ANTIMICROBIAL ACTIVITY - Johney, Jesteena; Eagappan, Kannan; Ragunathan, R. R. (International Journal of Current Pharmaceutical Research, 2016)
Objective: The aim of the present work was to extract the chitin and chitosan from two species of Pleurotus, its characterization and its antimicrobial activity against bacteria and fungi. Methods: The fungi were grown in MGYP medium for 15 d. The chitin and chitosan were extracted using the alkaline method and various biochemical methods and compared with commercial chitin and chitosan. The FTIR and SEM were also performed. Antimicrobial activity was performed using well diffusion method. Results: The maximum yield of mycelia and the chitin and chitosan were obtained on 12th day of incubation. P. folrida gave maximum yield (201.3 mg/l of chitin and 65.61 mg/l of chitosan). Fourier Transform Infrared spectroscopy comparing the results obtained with results for commercial chitin and chitosan. Our results showed that chitin and chitosan obtained from Pleurotus spp. had a significant similitude with commercial. SEM image also carried out to study the surface morphology. The fungal chitin and chitosan had more antimicrobial activity against the gram+ve, gram–ve and the various fungus. Conclusion: In the present study the chitin and chitosan were extracted from the Pleurotus spp. (P. florida and P. eous). The yield was maximum in P. florida after 12thday of fermentation. The FTIR and SEM also confirmed the chitin and chitosan. The extracted chitin and chitosan were subjected to antimicrobial activity, and it was found the extracted chitin and chitosan were active against the bacteria and fungi. Our findings suggest that the Pleurotus spp. are the potential candidate to produce eco-friendly chitin and chitosan in the development of drugs, artificial bone and raw material for the food industries in the near future.